ANALISIS PENGUKURAN RASIO KEUANGAN TERHADAP PROFITABILITAS BANK UMUM SWASTA NASIONAL (BUSN) NON DEVISA - Sihotang, Ellen Theresia; Ngempeng, Fortunata Yuni Artati; Rokhmania,; Meidiaswati, Harlina (Universitas Negeri Surabaya, 2023)
Banks, as intermediaries in their operational activities, have to gain the trust of the public. One way to gain this trust is through measuring the bank’s financial performance. The purpose of this study is to analyze the simultaneous and partial effects of Asset Ratio (LAR), Non-Performing Loan (NPL), Interest Rate Ratio (IRR), Cost Income Ratio (CIR), and based Income Ratio (FBIR) on Return on Asset (ROA). This study used judgment sampling with four samples from the Non-Foreign Exchange National Public Private (BUSN) population. The period of study is from 2015 to the second quarter, 2022. The result of this study revealed that LAR, NPL, IRR, CIR and BIR are simultaneously significant on ROA. LAR is partially positive and significant on ROA. IRR and CIR are partially negative and significant on ROA. NPL and FBIR are partially not significant on ROA because the percentage of interest-income earned is smaller due to a large number of non-performing loans. CIR is the most influential variable in the decrease of ROA. The implication of this study on the banking industry is that banks have to pay attention to the level of liquidity of their total assets. Efficiency of operating costs and paying attention to market interest rates on lending and funding to maximize profit and income and increase ROA.